“Triple bottom line” as “sustainable corporate performance”: a proposition for the future - Fauzi, Hasan; Svensson, Goran; Abdul Rahman, Azhar (2010)
Based upon a review of corporate performance, corporate financial performance and corporate social performance, we propose that the concept of ―triple bottom line" (TBL) as ―sustainable corporate performance" (SCP) should consist of three measurement elements, namely: (i) financial, (ii) social and (iii) environmental.TBL as SCP is proposed to be derived from the interface between them.We also propose that the content of each of these measurement elements may vary across contexts and over time.Furthermore, TBL as SCR should be interpreted to be a relative concept that is dynamic and iterative.Continuous monitoring needs to be performed, adapting the content of the measurement elements to changes that evolve across contexts and over time in the marketplace and society.TBL as SCP may be seen as a function of time and context.